Predicted Economic Benefits of a Novel Biomarker for Earlier Sepsis Identification and Treatment: A Counterfactual Analysis. (August 2019) - Paoli, Carly J.; Reynolds, Mark A.; Coles, Courtney; Gitlin, Matthew; Crouser, Elliott
Abstract : Objectives: To estimate the potential clinical and health economic value of earlier sepsis identification in the emergency department using a novel diagnostic marker, monocyte distribution width. Design: The analysis was conducted in two phases: 1) an analysis of the pivotal registration trial evidence to estimate the potential benefit of monocyte distribution width for early sepsis identification and (2) a cost-consequence analysis to estimate the potential economic and clinical benefits that could have resulted from earlier administration of antibiotics for those patients. Setting: Sepsis identified in the emergency department which led to inpatient hospitalizations. Patients: Adult sepsis patients admitted through the emergency department. Interventions: None. This was a model simulation of clinical and economic outcomes of monocyte distribution width based on results from a noninterventional, multicenter clinical trial. Measurements and Main Results: Among the 385 patients with sepsis, a total of 349 were eligible for inclusion. Sixty-seven percent of patients were predicted to benefit from monocyte distribution width results, resulting in an estimated mean reduction in time to antibiotics administration from 3.98 hours using standard of care to 2.07 hours using monocyte distribution width + standard of care. Based on this simulated reduction in time to antibiotics, monocyte distribution width + standard of care could have resulted in a less than or equal to 14.2% reduction (27.9% vs 32.5%) in mortality, a mean reduction of 1.48 days (10.0 vs 11.5 d) in length of stay, and $3, 460 ($23, 466 vs $26, 926) savings per hospitalization. At the hospital level, based on an established national mean of 206 sepsis hospitalizations per hospital per year, earlier identification with monocyte distribution width is predicted to result in a total of $712, 783 in annual cost savings per hospital. Conclusions: Improved early identification of sepsis using monocyte distribution width along with current standard of care is estimated to improve both clinical and economic outcomes of sepsis patients presenting in the emergency department. Further research is warranted to confirm these model projections.